Towards the Standardization of Graduation Profiles in Doctoral Programs - Núñez-Valdés, Karen (2019)
This article presents the analysis of the graduation profiles declared by the Education Doctoral programs in Chilean territory. This process was carried out in accordance with a Standard Graduation Profile, which spells out the competencies that a future doctor must possess after training. This profile includes the competences required in the current globalized context, taking into consideration national and international documentation, as well as the opinions of the doctoral students. Accordingly, it intends to analyze the consistency of each of the declared graduation profiles with respect to the standard graduation profile. The nature of the method used is descriptive and quantitative, with a cross-sectional design, using descriptive and association techniques. The results include the quantification of the disciplinary, methodological, instrumental, and generic competencies declared in the graduation profiles of the Education Doctoral programs in Chile, with the aim of contributing to their assessment within the national context. At the international level, a replicable methodology is presented for the analysis of the graduation profiles in doctoral programs.